STRUCTURAL ORGANIZATION PERSONAL REFLEXION - Фурман, В. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2013)
This article examines the issues shaping personal reflexion students, structural components, features, and level of deployment reflektyvnosti presented model of personal reflection